Role Of Multinational Companies In The Multimedia Super Corridor Cluster: Case Studies Of Nokia And NTT MSC - Ching, Long Hui (2002)
The purpose of this study is to investigate the role of multinational companies in the growth and dynamism of the Multimedia Super Corridor cluster. Whilst the study of clusters and MNCs is not new, none has been carried out on the MSC in particular, or o